The drive behind the veil: the motivation behind female suicide bombers narrative of violence in the novel Bride of ISIS - Abdullah, Amalia Qistina Castaneda; Talif, Rosli; Kaur, Hardev; Awang, Mohammad Ewan (Faculty of Communication and Media Studies, Universiti Teknologi Mara, 2018)
Female suicide bombing is complicated, comprising of multifaceted aspects that defy simple explanation. Female suicide bombers who become involved in jihad have a myriad of inner conflicts fuelled by their psychopathology and demands of a shame-honour culture. This research aims to demystify female suicide bombers’ behaviour from a psychoanalytic perspective called death drive. It sheds light on the volatile amalgamation of factors inherent in being raised in a shame-honour culture and religion. It intends to help readers understand female suicide bombers’ behaviour using the tools and insights drawn from psychoanalysis. Death drive is not like the Buddhist belief of striving for annihilation for eternal peace. According to Lacan, in death drive, there is a struggle within the psyche between the conscious mind that is supposed to control the body and the body itself. For female suicide bombers, the reality is how they are programmed with ideology and filial piety, that leads them to an imaginary eagerness that drives them to sacrifice their lives for eternal glory and honour and the symbolic structure that puts the programming in their heads. Through the selected novel, this research seeks to shed light on how transparent, stark and revealing their unconscious behaviour is. To understand where this aberrant behaviour arises and what its “drivers” are – externalised and projected through repression and senseless murderous rage.